PANEN DAN PASCAPANEN PADI, JADUNG DAN KEDELAI - Molenaar, Robert (EUGENIA, 2020)
Current post-harvest procedures for food crops are lacking, mostly due to the shortage of adequate postharvest facilities and technology, outdated knowledge and skills of the farmers, and lack of awareness of more modern post-harvest handling. Furthermore, farmers have yet to understand and experience the benefits of post-harvest procedures that can increase crop quality. Harvest and post-harvest procedures for food crops are a strategic step in supporting national food security. Post-harvest procedures directly decrease losses, maintain quality, and increase farmer profits and competitiveness. Surveys by Statistics Indonesia (2012) showed that the national conversion rates of Harvested Dry Grain to Milled Dry Grain are 83,26%, while national conversion rates of Milled Dry Grain to rice are 62,47%. This illustrates a national loss potential throughout the conversion chain, estimated to be 40 billion Rupiahs every year. Efforts to improve harvest and post-harvest procedures for foor crops (with good technological support) need to be targeted towards three things (1) reduction of loss; (2) increase of quality and competitiveness (standardize processes and yield quality); (3) increase of farmer welfare. For this reason, the participation of all postharvest stakeholders is required in standardizing the process and yield quality in post-harvest processes.